Gas 222Rn Sebagai Perunut Gas CO2 Dari Dalam Tanah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
1. 222Rn occupies 40% of the universal radiation dose. On the other hand, CO2 is the main green house gas. Both gases are emanated togetherftom soil and affected by the environmental conditions. This research was conducted to study the emanation pattern of 222Rn and CO2 by the accumulation method and the use of of 222Rn as tracer gas for concentration change of CO2 emanated from soil. A top sealed plastic container was used as an accumulator and embedded into 20 cm depth soil. The influences of some environmental conditions that were air pressure, air temperature, air humidity, and soil temperature, on the emanation rate of both gases were also examined. 222Rn concentration was detected by a passive method portable radon monitor "AlphaGUARD" PQ-2000 at one-hour measurement interval. AlphaEXPERT" version 3.0 software was used to record the data from "AlphaGUARD" monitor. CO2 concentration in air was measured by an infrared method CO2 monitor TG-1300 A and recorded by Pegasus !NR-6041 recorder. This recorder was also used to record the soil temperature measured by a thermoelectric couple. The 222Rn and CO2 concentrations on the container fluctuate in the same pattern that are affected by the variation of air pressure and soil temperature. After the gases fulfilled the container, the back diffusion resulting in the decreasing of gases emanation rate occurs.